2017
DOI: 10.3389/fmicb.2017.01007
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Soil Microbial Community Structure Associated with Different Legume Species Is Greater than that Associated with Different Grass Species

Abstract: Plants are the essential factors shaping soil microbial community (SMC) structure. When most studies focus on the difference in the SMC structure associated different plant species, the variation in the SMC structure associated with phylogenetically close species is less investigated. Legume (Fabaceae) and grass (Poaceae) are functionally important plant groups; however, their influences on the SMC structure are seldom compared, and the variation in the SMC structure among legume or grass species is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 66 publications
10
50
0
1
Order By: Relevance
“…Considering the lower bacterial abundance involved in OA biosynthesis and transport in stylo soil, it appears that plant hosts and their associated bacteria are likely complementary in producing OAs to solubilize sparingly soluble Pi. Alternatively, it is likely that fungi take over the bacterial function of P solubilization in stylo soil because fungi are more abundant in legume soil than in grass soil (Turner et al ., ; Zhou et al ., ). P solubilization by fungi is well recognized (Whitelaw, ; Mondala et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Considering the lower bacterial abundance involved in OA biosynthesis and transport in stylo soil, it appears that plant hosts and their associated bacteria are likely complementary in producing OAs to solubilize sparingly soluble Pi. Alternatively, it is likely that fungi take over the bacterial function of P solubilization in stylo soil because fungi are more abundant in legume soil than in grass soil (Turner et al ., ; Zhou et al ., ). P solubilization by fungi is well recognized (Whitelaw, ; Mondala et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Legumes and grass are distinct functional groups in diverse ecosystems. Our data support the different bacterial community composition associated with stylo (legume) and bahiagrass (grass), consistent with previous reports (Turner et al ., ; Zhou et al ., ). This difference further leads to divergent functions in P cycling in stylo soil and bahiagrass soil.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Remarkable difference in rhizosphere microbiome was observed between clover and maize (Figure 3), which confirms previous studies on microbial communities in the rhizosphere of different crops. Legume and grass differentially select microbial communities (Zhou et al, 2017). Long-term (12 years) cover cropping with four leguminous species significantly enhanced soil microbes that were related with N and C metabolism (Dinesh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial 16S rRNA gene is approximately 1,500 bp in length with nine highly conserved regions. The V3 and V4 regions are routinely sequenced using Illumina technology for determining the microbial community composition, which has been proved to be a reliable approach (Ding et al, ; PĆ©rezā€Jaramillo et al, ; Wang et al, ; Zhou, Zhu, Fu, & Yao, ). Our sequencing data indicated that the dominant groups across all samples were Actinobacteria, Proteobacteria, and Planctomycetes (Figure ).…”
Section: Discussionmentioning
confidence: 99%